When a pre-embryo exists, it is another embryo - Zatti, Mario (Medicina e Morale, 1991)
The human organism, even at the beginning of its development, is an expression of individual life, and its characteristics are unity and defined limitation of the self. This is why, when twinning accidentally occurs, the life of the pre-existing organism is suppressed and two new lives come into being.